Innovation of PATUH SEHAT Service as a Palliative Care Service Program at Jember Pulmonary Hospital: Inovasi Layanan PATUH SEHAT sebagai Program Layanan Perawatan Paliatif di Rumah Sakit Paru Jember - Ika Mardiyah; Tantut Susanto; Desy Iswari (Journal of Community Empowerment for Multidisciplinary (JCEMTY), 2024)
Advances in treatment have led to longer survival and an increase in the number of women living with metastatic breast cancer (MBC) in the United States. In palliative care, symptoms are multiple and combined, evolving and changing, with multidimentional character and multifactorial causes, and high prevalence, negatively impacting the quality of life of patients and their families. Nurses providing palliative care need to recognize and respond effectively to their patients' symptoms, integrate systematic care plans with technology systems and apply them to the care of patients with chronic obstructive pulmonary disease (COPD) and respiratory failure and explore a continuous care model based on modern technology to improve the quality of life of COPD and respiratory failure aimed at alleviating COPD symptoms, reducing the number of acute episodes of COPD and improving the quality of life of patients. One hundred patients with COPD and respiratory failure who were treated in the respiratory medicine department of a territorial hospital were selected and categorized into control and experimental groups. Audit and feedback tools. Practical application using the Joanna Briggs Institute Clinical Evidence System (JBI PACES) and Getting Research into Practice (GRiP). Nurses were given a pre-test, exposed to socialization materials and given a post-test. From 9 nurses in the room who implemented the material, it can improve the practice of the nursing team in monitoring and managing symptoms of palliative care patients, so that it has a positive impact on the quality of life of patients and their families. The criteria for change are sig values ​​≤ 0.05, while if sig > 0.05 then there is no difference in the values ​​observed after implementation. Validated is an indicator of the quality of physical aspects of care which is part of the process indicators in palliative care. The creation of SOPs, discharge planning and online-based innovations can improve understanding of palliative care, service modification with PATUH for patients and SEHAT for nurses with the formation of the Si MANIS g-form, barcode with MANISAN, nurse assessment with online media g-form and socialization, are promotive, preventive, curative and rehabilitative efforts.